Socioemotional wealth in family business research : A systematic literature review on its definition, roles and dimensions (2022)
ABSTRACT: This study aims to depict the current state of research on socioemotional wealth (SEW) in family businesses considering its definitions, roles, and dimensions. Using the SPAR-4-SLR protocol (Paul, Lim, O’Cass, Hao, & Bresciani, 2021), we develop a systematic review of literature on SEW covering 74 studies published between 2007 and 2022. We propose a comprehensive definition of SEW based on four nonfinancial aspects and an association model that reviews the roles of SEW as an antecedent, a consequence, or a moderator. We also offer a new conceptual model for SEW comprising a general dimension and ten specific dimensions to facilitate empirical inquiries into areas beyond those considered by extant SEW models. Finally, we highlight avenues for future research, emphasizing opportunities to advance the understanding of SEW in family business research.